Leta Semadeni's Romansh‐German poetry: Poetic praxis between languages - McClelland, Richard (Orbis litterarum, 2025)
Swiss poet Leta Semadeni's award‐winning literary work is shaped in and through her bilingualism. Her poetry combines her ‘mother tongue’, the Romansh idiom Vallader, and her ‘first great love’, German. Her writing is shaped by a linguistic terseness and a layering of images of everyday experience with meditations on the deeper realities underpinning contemporary life. In this study, I explore the self‐translational dynamics that shape Semadeni's bilingual writing and consider how these dynamics are manifest in and shape her writing. This is explored in relation to a thematisation of the writing process that Semadeni presents in a series of poems in the collection In mia vita da vuolp/In meinem Leben als Fuchs (In My Life as a Fox, 2010). As I propose, because Semadeni works dialectically across Vallader and German, her poems should be understood and read as a bilingual whole with a dual linguistic and cultural origin. This results in poetry that explores both the multilingualism that marks life in Semadeni's native Engadin valley and the hybrid creativity that this precipitates.